الاتجاهات الحديثة والكلاسيكية في المعجم العربي-الإندونيسي: دراسة تحليلية مقارنة لقاموس نجوى ثرايا والقاموس الغني: Modern and Classical Trends in Arabic–Indonesian Lexicography: A Comparative Analytical Study of Najwa Thuraya Dictionary and Al-Qamus al-Ghani - RD, Zabrina Aprillia; Zain, Muhammad Alfa; E.A, Adinda Mutiara; Bahruddin , Uril (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2025)
Abstract: This study aims to conduct a comparative analysis of the Najwa Thuraya Dictionary and the Al-Ghani Dictionary, two widely used references in Arabic language teaching and research. Employing a qualitative descriptive–comparative approach, the study analyzes selected dictionary entries through document analysis. The findings indicate that the Najwa Thuraya Dictionary emphasizes simplicity and practical contemporary vocabulary, making it suitable for beginner-level learners, whereas the Al-Ghani Dictionary offers broader linguistic coverage and greater depth, serving as a more comprehensive academic reference. The study concludes that each dictionary fulfills a distinct function, with Najwa Thuraya being more effective in educational contexts and Al-Ghani more appropriate for scholarly use.